The Role of Oncology Clinical Nurse Specialists in Enhancing Cancer Survivorship Care: A Comprehensive Review of Global Implementation Challenges and Opportunities - Alruwaili, Maram Nasser Awaida; Alruwaili, Awatif Rakyan Murayr; Alanzy, Fatmah Maskor Koder; Alenazy, Aamal Shamat; Alrwaili, Amna Khaled Jelbakh; Alenazi, Badriaha Reda Abdulah; Alruwaili, Sultanah Rakyan M; Alruwaili, Majed Naser Awaida; Alrowaily, Afrah Esmaail; Alshammari, Nawaf Reden; Almutairi, Mashael Tala Taye; Alghamdi, Abdulmalek Ali (Journal of Ecohumanism, 2024)
Background: The role of oncology clinical nurse specialists (CNS) has become increasingly vital in the landscape of cancer care, especially as healthcare systems adapt to the growing demands of cancer survivorship. These advanced practice nurses provide critical support throughout the cancer journey, emphasizing symptom management, patient education, and coordination of care. Methods: This literature review employed a Rapid Evidence Assessment methodology, focusing on peer-reviewed articles published between 2022 and 2023. The review analyzed the global implementation of the oncology CNS role, examining various healthcare systems and the unique challenges associated with this position. Results: The findings indicate that oncology CNSs significantly enhance patient outcomes, including reduced hospitalizations and improved quality of life for cancer patients. In the UK, for instance, data revealed a substantial decrease in non-acute hospitalizations among lung cancer patients under CNS care. Qualitative research highlighted the emotional support provided by CNSs, which is crucial for patients navigating complex treatment regimens. Challenges identified include role ambiguity, insufficient training, and systemic barriers that hinder effective practice. Conclusion: The oncology CNS role is essential for improving cancer care delivery, yet it faces significant challenges that limit its potential. To optimize the impact of CNSs, healthcare systems must clearly define their responsibilities, enhance training programs, and foster collaboration among multidisciplinary teams. This review underscores the need for further research to fully understand the contributions of oncology CNSs in diverse healthcare settings, as well as to identify strategies for overcoming existing barriers.